How Many People Are Exposed to Suicide? Not Six. Issue 2 (7th March 2018) - Cerel, Julie; Brown, Margaret M.; Maple, Myfanwy; Singleton, Michael; van de Venne, Judy; Moore, Melinda; Flaherty, Chris
Abstract : It has long been stated that six people are left behind following every suicide. Despite a lack of empirical evidence, this has been extensively cited for over 30 years. Using data from a random‐digit dial survey, a more accurate number of people exposed to each suicide is calculated. A sample of 1, 736 adults included 812 lifetime suicide‐exposed respondents who reported age and number of exposures. Each suicide resulted in 135 people exposed (knew the person). Each suicide affects a large circle of people, who may be in need of clinician services or support following exposure.